MEMANGGUNGKAN KISAH TANTRI ALIH WAHANA DALAM PERTUNJUKKAN PRAGMENTARI TANTRI GONG KEBYAR ANAK-ANAK DUTA KABUPATEN KLUNGKUNG, PESTA KESENIAN BALI 2018 - I Kadek Surya Jayadi (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
Tantri is one of the Balinese literature, which is well known and has its own impression. This special impression arises because of its substance, which makes animals the main figures in the storytelling and is rich in religious literary values. Because of the impression it gave, tantri works appeared in various forms. In addition, tantri literature is packaged in other works, one of which is the Tantri Dance Fragment. This study is a study of the fragmentary tantri "Panas Dalem'' presented by the gong kebyar children's sekeha gong kebyar anak-anak of Klungkung Regency at the 2018 Bali Arts Festival (Pesta Kesenian Bali). Using the textual transformation method, this study tries to analyze the transformations carried out by comparing them with I Made Pasek's Tanri Literature. The results of the study show that there are several differences, such as adding and removing the characters, inserting the elements of comedy, and changing the ending of the story